2015
DOI: 10.1016/j.bpj.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Alters the Morphology and Toxicity of Aortic Medial Amyloid

Abstract: The aggregation and fibril deposition of amyloid proteins have been implicated in a range of neurodegenerative and vascular diseases, and yet the underlying molecular mechanisms are poorly understood. Here, we use a combination of cell-based assays, biophysical analysis, and atomic force microscopy to investigate the potential involvement of oxidative stress in aortic medial amyloid (AMA) pathogenesis and deposition. We show that medin, the main constituent of AMA, can induce an environment rich in oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 50 publications
8
27
0
Order By: Relevance
“…5)), and could assist in driving the extension of the C-terminal β-strand as indicated in Figs 4 and 5. In addition, we recently showed that medin can be nitrated at positions Y16 and W11/W22 with subsequent alterations in aggregation properties38. The model proposed here is consistent with all of these sites being accessible for modification altering the ability of the protein to assemble through intermolecular facial β-sheet interactions (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…5)), and could assist in driving the extension of the C-terminal β-strand as indicated in Figs 4 and 5. In addition, we recently showed that medin can be nitrated at positions Y16 and W11/W22 with subsequent alterations in aggregation properties38. The model proposed here is consistent with all of these sites being accessible for modification altering the ability of the protein to assemble through intermolecular facial β-sheet interactions (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…However, hyperglycemia was not observed in the older-aged subjects examined in the present study, suggesting that the stronger expression of CML in the older-aged group was associated with oxidative damage. These findings might be associated with arterial stiffness of older-aged individuals, as reported by Semba et al 23 As deposition of medin caused injury of SMC, 17 and SMC in the aortic media were decreased with aging, 1,24 it is consistent with the decrease of α-actin, a marker protein of SMC, in older-aged aortic media. It is known that remodeling of the extracellular matrix, such as elastin, collagen and glycosaminoglycan, was caused by aging.…”
Section: Discussionsupporting
confidence: 67%
“…c,d) and CML (Fig. e,f), were examined . Few regions of SMC nuclei were stained positive for 8‐OHdG in young individuals, whereas most nuclei were positive in older‐aged individuals (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, we report for the first time that the mechanism, or one of the mechanisms, by which NLGM1 protects against LC endothelial injury is through Nrf‐2–mediated upregulation of antioxidant stress responses (HO‐1 and NQO1), leading to reduced oxidative and nitrative stress and increased NO bioavailability. Because we previously demonstrated that oxidative and nitrative stress underlie microvascular injury induced by amyloid proteins (LC in AL, β‐amyloid in Alzheimer's disease, and medin in aortic medial amyloidosis), the induction of an antioxidant stress response by NLGM1 may have potential clinical relevance not only to AL but also to other amyloid diseases.…”
Section: Discussionmentioning
confidence: 99%